The Use of Preloved Media in Improving Environmentally Friendly Attitudes at Pertiwi Kayuagung Kindergarten - Kartini Kartini; Heny Wulandari; Kanada Komariyah (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
Early childhood education plays an important role in shaping children’s behavior and perspectives toward their surrounding environment. One effort that can be made to foster environmental awareness from an early age is through the use of recycled or preloved materials as learning media. Pertiwi Kindergarten in Kayuagung has implemented the use of preloved media in teaching and learning activities to encourage children’s creativity while instilling environmentally caring attitudes. This study aims to examine teachers’ efforts in enhancing environmentally friendly attitudes among early childhood learners through the use of recycled materials, as well as to explore their impact on children’s creativity and environmental awareness. This research employs a descriptive qualitative method with data collection techniques including interviews, observations, and documentation. This approach was chosen to gain an in-depth understanding of the experiences of teachers and children in using preloved media as learning tools at Pertiwi Kindergarten, Kayuagung. The data obtained were analyzed descriptively to illustrate the process and impact of implementing preloved media in learning activities. The results indicate that the use of preloved media contributes significantly to improving children’s creativity and instilling environmentally friendly attitudes. Children learn to utilize recycled materials creatively, understand the importance of sustainability, and develop fine motor skills, social skills, and problem-solving abilities. Thus, preloved media have proven to be effective in supporting the development of creativity and environmental awareness in early childhood